749The global prevalence of Rheumatoid Arthritis: A meta-analysis. (2nd September 2021) - Almutairi, Khalid; ,; ,; ,; ,
Abstract: Background: To determine the global prevalence of rheumatoid arthritis (RA) based on published studies and reveal factors which influence the RA prevalence estimates. Methods: Four electronic databases- ProQuest Central, MEDLINE, Web of Science, and EMBASE were searched for publications from 1980 and 2019, reporting prevalence estimates of RA. A random-effect meta-analysis model was used to produce the pooled prevalence estimates. The potential sources of between-study heterogeneity were identified using sensitivity analysis, sub-group and meta-regression analyses. Results: A total of 67 studies consisting of 212, 335, 171 patients were included in the meta-analysis. The global prevalence of RA was estimated 0.46% (95% CI: 0.39-0.54; I 2 =99.9%) with a 95% prediction interval (0.06–1.27). The point-prevalence of RA was 0.45% (95% CI: 0.38- 0.53%), while the pooled period-prevalence was 0.46% (0.36% and 0.57%). The highest RA pooled prevalence was estimated at 0.69% (95% CI: 0.47–0.95) derived from linked data sources studies. Based on subgroup analyses, the pooled prevalence of RA was influenced by geographical location, the risk bias of studies, period-prevalence method and urban population setting over the stratified periods. Conclusion: The global prevalence of RA was 460 per 100, 000 population from 1980–2018, with a 95% prediction interval (0.06– 1.27%). RA prevalence estimates were influenced by geographical location, the risk bias assessment of studies, period-prevalence method and urban population setting over time. Key messages: The global prevalence of RA was 460 per 100, 000 population from 1980–2018, with a 95% prediction interval (0.06– 1.27%).